An Improved Cr-EA-IRMS Method for the Effective Determination of the Hydrogen Isotopes in Coal Samples - Li, Hongwei; Feng, Lianjun (Frontiers in Chemistry, 2022)
Hydrogen isotopes in coal are of great significance for studying the geochemical evolution process of coal. The analysis methods are mainly divided into dual-inlet method and continuous flow method. The organic hydrogen of coal is converted into water, and then purified, separated, and reacted with the reducing agent to generate hydrogen. The hydrogen is collected and analysis of the H2 gas has been performed with a dual-inlet isotope ratio mass spectrometry (DI-IRMS). The dual-inlet method is complicated and inefficient. The continuous flow method is based on the high temperature conversion (HTC) technique using an elemental analyzer with a glassy carbon tube and filling (temperature conversion/elemental analysis, TC/EA-IRMS). Problematic results would be generated due to interference with quantitative conversion of organic hydrogen to molecular hydrogen. In this paper, the combined use of an improved element analyzer with chromium powder in the reactor and ratio isotope mass spectrometry (Cr-EA-IRMS method) eliminates the problems caused by the TC/EA method and realizes accurate and rapid analysis of samples. Meanwhile, The hydrogen isotopes of coal samples from different regions were analyzed, and displayed obvious regional characteristics.